POSITIVE DISCIPLINE: SOLUTION TO BOOST STUDENTS’ SELF ESTEEM IN LEARNING ENGLISH AS FOREIGN LANGUAGE - Nur Muthmainnah (ENGLISH, 2021)
This theoretical concept is aimed to investigate how positive discipline is implemented in foreign language classroom and improve students’ self-esteem. As one of forms of classroom management, positive discipline expects long-term discipline planted in the learners’ behavior. There are five principles of positive discipline which can be implemented in language learning; Identifying long-term goals; Providing warmth and structure; Understanding child development; Identifying individual differences; Problem-solving and responding with positive discipline. The implementation of positive discipline which support classroom encouragement and confidence could improve learner’s self-esteem. By implementing the positive discipline, teacher also takes advantages on understanding more about his students’ character. In addition, learner would realize their long-term goal of learning foreign language which motivates them to be more active in the class.